Integration of curriculum ideology and politics in higher education: a case study of English linguistics in China - Mei, Zhixing (Frontiers in Education, 2024)
Amidst efforts to fulfill the Chinese government's education guide for morality building and character cultivating, curriculum ideology and politics have emerged as key aspects in higher education pedagogy. English linguistics, a staple for junior English majors and often perceived as theoretical and challenging, represents an opportunity to align with national education directives. This study explores the integration of ideological and political education within the English major's curriculum, specifically within an English linguistics course. This paper details an empirical case study conducted in a local Jiangxi university in China, where an " ideological education+linguistics " teaching model was carefully crafted and implemented in the introductory linguistics session. Methodologies included classroom observation, post-lesson questionnaire and interview, revealing enhancements in student engagement, understanding of linguistic concepts, and scientific and logical reasoning. Additionally, noteworthy improvements in teaching methodologies were reported. The findings affirm the model ' s feasibility and effectiveness in reinforcing the curriculum ideology and politics in major disciplines, suggesting a beneficial tripartite impact on national educational goals, student learning, and teaching innovation. Research significance indicates that by applying their experiences, front-line teachers can act as researchers, enhancing the implementation of educational research; besides theoretical studies, micro case studies are essential to validate and complement educational research, thus contributing to the development of a comprehensive theoretical framework.